Evaluation of the penetration depth of Guttaflow bioseal and Bioceramic sealers using scanning electron microscope (in vitro study). - Razawa Kareem Saeed (Erbil Dental Journal)
Background and objective: Three- dimensional obturation of the canal is mandatory in root canal treatment to decrease failure rate, the major cause of root canal reinfection after obturation is insufficient obturation of the canal which later leads to a periapical lesion and reinfection.This study aimed to evaluate the penetration depth of Guttaflow bioseal and Bioceramic sealer. Methods: Twenty extracted single-rooted human teeth (mandibular first premolar) were used in this study, teeth were decornated leaving 10 mm root length. The chemico-mechanical preparation of the samples was done by using a protaper universal system till size F1 and then samples were divided into 2 groups (n = 10), according to the filling material in the first group Guttaflow bioseal used while in the second group Onefil bioceramic sealer used the sealers introduced into canals according to manufacturer instructions and then obturated with gutta-percha size F1, single condensation technique used and finally samples were cross-sectioned at 3 and 7 mm, sealers penetration depth was measured by using scanning electron microscope. Result: Independent sample t-test shows that the difference between the penetration depth of guttaflow bioseal and bioceramic sealers are non-significant while the ANOVA test shows that the difference between the three sections of the root is highly significant for both sealer, coronal section shows the best result for Guttaflow bioseal while middle section for Bioceramic shows the best result of penetration. Conclusion: There are no difference in sealer penetration of both sealers Guttaflow bioseal and Onefil bioceramic, while regarding sealer penetration in each sections of root for Guttaflow bioseal in coronal section shows a best penetration, for Onefil bioceramic middle section shows a best penetration.